2023
DOI: 10.1371/journal.pone.0277030
|View full text |Cite
|
Sign up to set email alerts
|

Electromyographic analysis of the stomatognathic system of children with Molar-incisor hypomineralization

Abstract: Introduction Molar-incisor hypomineralization (MIH) is a qualitative defect of dental enamel that affects one or more permanent first molars, with or without involvement of the incisor teeth. This condition leads to challenges to dental care and treatment planning. Aim Based on the hypothesis that children who have MIH possibly present alterations in postural and masticatory activities and considering the absence of studies investigating these parameters, the present study evaluated the functionality of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 63 publications
1
12
0
Order By: Relevance
“…Thus, it is suggested that this may have possibly occurred due to the severity of the disease not being severe enough to resist using the affected side. When this enamel anomaly presents a higher degree of hypersensitivity or fracture, children tend not to use the affected side, but rather the other side for comfort in both biting and chewing [20,49].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, it is suggested that this may have possibly occurred due to the severity of the disease not being severe enough to resist using the affected side. When this enamel anomaly presents a higher degree of hypersensitivity or fracture, children tend not to use the affected side, but rather the other side for comfort in both biting and chewing [20,49].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical consequences associated with MIH include hypersensitivity [2,[11][12][13], di culty in achieving anesthesia [14,15], and negative aesthetic impacts [16][17][18]. Fractures after tooth eruption and rapid caries progression in newly erupted rst permanent molars may occur [19], predisposing the patient to chewing preference and leading to stomatognathic system alterations [20].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Different methods for evaluating chewing patterns have been proposed, some aiming to study functionality and chewing e ciency, while others assess issues related to chewing dynamics. In the rst group, studies stand out that use surface electromyography, devices measuring bite force, and technologies allowing evaluation of jaw movements and/or occlusal dynamics [7,36,8,9,37]. Research related to dynamics include the assessment of chewing performance, quanti cation of dental functional units, and the PCS [38,13,[39][40][41].…”
Section: Discussionmentioning
confidence: 99%